2014
DOI: 10.1128/cvi.00374-14
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus-Specific Neutralizing IgM Antibodies Persist for a Lifetime

Abstract: c Detection of immunoglobulin M (IgM) antibodies has long been used as an important diagnostic tool for identifying active viral infections, but their relevance in later stages has not been clearly defined in vivo. In this study, we followed the kinetics, longevity, and function of influenza virus-specific IgM antibodies for 2 years following sublethal infection of mice with live mouseadapted A/PR/8/34 virus or immunization with formalin-inactivated virus. These groups mounted robust protective immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…The vaccine formulation containing the low dose of CpG 2007 elicited the highest IgM antibody titre at day 28 and significantly exceeded the immune responses generated by the AddaVax TM (squalene) and CpG 1826 vaccine formulations. IgM antibodies are particularly important in providing early protection against influenza virus infections [28]. While limited information on the importance of influenza induced IgM antibody responses in chickens is lacking, Qui and colleagues [29] have suggested that in humans the extent of this response may be important in predicting virus clearance rates and can influence later IgG antibody responses.…”
Section: Discussionmentioning
confidence: 97%
“…The vaccine formulation containing the low dose of CpG 2007 elicited the highest IgM antibody titre at day 28 and significantly exceeded the immune responses generated by the AddaVax TM (squalene) and CpG 1826 vaccine formulations. IgM antibodies are particularly important in providing early protection against influenza virus infections [28]. While limited information on the importance of influenza induced IgM antibody responses in chickens is lacking, Qui and colleagues [29] have suggested that in humans the extent of this response may be important in predicting virus clearance rates and can influence later IgG antibody responses.…”
Section: Discussionmentioning
confidence: 97%
“…The aim of the current study was to evaluate the ability of the flagellin adjuvanted inactivated influenza vaccine to promote a long-lived IgG and IgM antibody responses in an independent group of infant animals (as those in our initial study were necropsied following challenge). We assessed IgG and IgM responses as both are reported to contribute to neutralization of influenza virus [35, 36]. The results presented here demonstrate increased influenza-virus specific IgG, although not IgM, responses at 6 months following vaccination in infants administered IPR8+flagellin compared to those that received IPR8 containing an inactive form of flagellin (m229).…”
Section: Introductionmentioning
confidence: 91%
“…Along with IgA, IgM antibodies are also secreted actively across the mucosa and may contribute to protection by preventing viral entry into the cells and also interfering with virus replication in the cells . The potential protective role of IgM antibodies is supported by a study in mice which has shown that IgM antibodies can neutralize influenza viruses in the presence of complement just as well as IgG antibodies …”
Section: Secretory Iga Production Upon Natural Influenza Infectionmentioning
confidence: 99%